2021
DOI: 10.3892/ol.2021.12570
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑15a‑5p inhibits endometrial carcinoma proliferation, invasion and migration via downregulation of VEGFA and inhibition of the Wnt/β‑catenin signaling pathway

Abstract: Endometrial carcinoma (EC) is one of the most common malignant gynecological tumors. Dysregulation of microRNAs (miRNAs/miRs) is frequently identified in human tumors, playing key regulatory roles in tumor growth and metastasis. The present study aimed to explore the functions and potential mechanisms of miR-15a-5p in EC progression. RT-qPCR was used to detect the expression levels of miR-15a-5p and vascular endothelial growth factor A (VEGFA) mRNA. Western blot analysis was performed to examine the expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…In lung adenocarcinoma, the expression of RUNX2 correlated with a poor hazard ratio, suggesting that RUNX2 plays a clinical role as an independent risk factor for poor survival in lung cancer [ 59 ]. A similar result demonstrated the positive correlation of elevated RUNX2 with poor overall survival of non-small-cell lung cancer patients [ 64 ]. RUNX2 expression was associated with adverse overall survival in a study of 301 renal cell carcinoma patients.…”
Section: Correlation With Clinical Outcomesupporting
confidence: 53%
“…In lung adenocarcinoma, the expression of RUNX2 correlated with a poor hazard ratio, suggesting that RUNX2 plays a clinical role as an independent risk factor for poor survival in lung cancer [ 59 ]. A similar result demonstrated the positive correlation of elevated RUNX2 with poor overall survival of non-small-cell lung cancer patients [ 64 ]. RUNX2 expression was associated with adverse overall survival in a study of 301 renal cell carcinoma patients.…”
Section: Correlation With Clinical Outcomesupporting
confidence: 53%
“…The Wnt signaling pathway is one of the most important signaling pathways during development of a number of tumors and other diseases, including embryonic development and maturation of the central nervous system ( 34 , 35 ). Increasing evidence has indicated miRNA dysregulation and the Wnt/β-catenin signaling pathway jointly drive carcinogenesis, cancer metastasis and drug-resistance ( 36 40 ). The present study reported that miR-433 inactivated the Wnt/β-catenin signaling pathway by targeting TMED5 in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, miR-652, miR-495, miR-1271, miR-381, and miR-29b have been identified as oncogenic miRNAs in EC (105,(154)(155)(156)160). Furthermore, miR-15a-5p and miR-589-5p were tumor suppressors in EC cells (161,164).…”
Section: Ec and Tumor Suppressor Mirnamentioning
confidence: 99%